NOVO COMPLEXO ENTRE NAFTOQUINONA NATURAL E ÍON Ag I : SÍNTESE E CARACTERIZAÇÃO - FAGANELLO, N. L.; CABEZA, N. A.; DE OLIVEIRA, T. D.; BROTO, D. F.; TEIXEIRA, E. I.; DOS ANJOS, A. (ANAIS DO ENIC, 2016)
-